Quantitative immunoenzymatic detection of viral encephalopathy and retinopathy virus (betanodavirus) in sea bass Dicentrarchus labrax. Issue 7 (27th November 2015) - Nuñez‐Ortiz, N; Stocchi, V; Toffan, A; Pascoli, F; Sood, N; Buonocore, F; Picchietti, S; Papeschi, C; Taddei, A R; Thompson, K D; Scapigliati, G
Abstract: Viral encephalopathy and retinopathy disease caused by betanodavirus, genus of the family Nodaviridae, affects marine, wild and farmed species including sea bass, one of the most important farmed species in Europe. This work describes a reliable and sensitive indirect ELISA assay to detect betanodavirus in biological samples using a polyclonal antiserum (pAb 283) against the 283/I09 virus strain, the most common red‐spotted grouper nervous necrosis virus (RGNNV) genotype in the Mediterranean area, and a capture‐based ELISA using a monoclonal antibody (mAb 4C3) specific to a common epitope present on the capsid protein. Using adsorbed, purified VERv preparation, the detection limit of indirect ELISA was 2 μg mL −1 (3 × 10 5 TCID50 per mL), whereas for capture‐based ELISA, the sensitivity for the antigen in solution was 17 μg mL −1 (35 × 10 5 TCID50 per mL). The capture‐based ELISA was employed to detect VERv in brain homogenates of in vivo infected sea bass and resulted positive in 22 of 32 samples, some of these with a high viral load estimates (about 1.1 × 10 8 TCID50 per mL). The ELISA system we propose may be helpful in investigations where coupling of viral content in fish tissues with the presence of circulating VERv‐specific IgM is required, or for use in samples where PCR is difficult to perform.